Preface: 9th International Seminar (MGIBR) Management and Genetic Improvement of Biological Ressources - Semir Bechir Suheil Gaouar; Rachid Azzi; Tarik Mohammed Chaouch; Mohammed Sidhoum; Ikram Mkedder; Mohammed Rida Mediouni; Sarra Selka; Djalel Eddine Gherissi; Amel Djaout; Hind Houssou; Hakim Tefiel (Biology and Life Sciences Forum)
Welcome to this volume dedicated to the conference “BIODIVERSITY: Food Security & Health”, the 9th International Seminar MGIBR, which was held on April 20, 21, and 22 in the conference room of the University of Tlemcen [...]